VENERATING SHAYKH ABD AL-QADIR AL-JILANI IN INDONESIA AND TURKIYE (State Islamic University (UIN) of Sunan Ampel Surabaya, 2024)
Shaykh Abd al-Qadir al-Jilani is a prominent figure in Muslim society. Compared to the influence of his intellectual works, the revered status he has earned is in large part because of his known outstanding spiritual qualities. He enjoys a place of honor that can hardly be equaled by other scholars and saints in Islam. The spread of this respect for him is not only a local phenomenon in Indonesia but also found in other countries. From the practice of venerating the shaykh in various places, it is known that the tradition has a global and a local dimension in the religious structure of Muslims. This issue is investigated through a comparative approach of textual and field studies in Indonesia and Turkiye. The study concludes that the preservation of the tradition of honoring the shaykh is possible because of the existence of supporting factors, such as the legacy of in the forms of books or institutions, the spread of documents or manuals that commemorate the figure, the development of communities that respect and practice his teachings, the emergence of rituals or activities associated with the figure on a regular basis. By those factors, the veneration becomes a popular and deep-rooted tradition.